2020
DOI: 10.3389/fgene.2019.01308
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Transcriptomic Analysis of Breast Muscle Development From the Embryonic to Post-hatching Periods in Chickens

Abstract: Skeletal muscle development and growth are closely associated with efficiency of poultry meat production and its quality. We performed whole transcriptome profiling based on RNA sequencing of breast muscle tissue obtained from Shouguang chickens at embryonic days (E) 12 and 17 to post-hatching days (D) 1, 14, 56, and 98. A total of 9,447 differentially expressed genes (DEGs) were filtered (Q < 0.01, fold change > 2). Time series expression profile clustering analysis identified five significantly different exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In the later stage of embryonic development, the number of differentially expressed genes decreased sharply. A similar gene expression pattern which we employed to assess muscle development after birth [20]. These ndings collectively provide evidence that the embryonic stage is the critical point of muscle development and the most extensive time of gene expression.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In the later stage of embryonic development, the number of differentially expressed genes decreased sharply. A similar gene expression pattern which we employed to assess muscle development after birth [20]. These ndings collectively provide evidence that the embryonic stage is the critical point of muscle development and the most extensive time of gene expression.…”
Section: Discussionmentioning
confidence: 55%
“…Notably, on the 12th day of embryonic development, muscle bers were yet to be formed (in the stage of fusion of multinucleated myotubes to form muscle bers), which was similar to the formation time of intact muscle bers in many local chicken breeds but took longer than fast-large broiler breeds [16]. A wealth of studies had shown that the embryonic period is a critical period for muscle development, during which the expression of muscle development-related genes was most active [17,18]. To elucidate the speci c variation of muscle development, we used the transcriptome analysis to explore the gene regulation network.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, 13 DEGs were enriched in the biosynthesis of amino acid pathway, of which 12 DEGs were upregulated in the breast muscle (Table S4). Another study found that genes related to glycolysis/gluconeogenesis and the biosynthesis of amino acid pathway were gradually upregulated during the growth and development of chicken breast muscle [63]. Therefore, we inferred that these DEGs were activated during fast-twitch muscle fiber formation.…”
mentioning
confidence: 79%
“…miR-NAs as important post-transcriptional regulators play essential roles in fine tuning gene expression dynamics [15,16]. We previously explored mRNA expression dynamics across chicken muscle developmental stages and found that there were distinct expression profiles in embryonic and post-hatching periods [14]. Therefore, to conduct a comprehensive study of miRNA expression dynamics and highlight key properties of miRNAs during chicken muscle development, we explored the expression patterns of miRNAs in chicken breast muscle from embryonic to post-hatching periods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these complex cell developmental processes during myofiber formation and hypertrophy, the fine-tuned regulation of numerous myogenic genes is also important for the development of skeletal muscle [4]. Our previous study also showed that there were distinct gene regulatory mechanisms of chicken muscle development between the embryonic and post-hatching periods, based on RNA sequencing of breast muscle tissue obtained from Shouguang chickens at 12-day embryo (E12), E17 and day 1 (D1), D14, D56 and D98 post-hatching stages [14]. However, a comprehensive study of the dynamics of miRNAs during chicken muscle development is lacking, especially from embryonic to post-hatching period.…”
Section: Introductionmentioning
confidence: 91%